(untitled) (International Journal of Engineering Sciences & Management Research, 2018)
A new guargum based resin containing 5-amino-1-naphthol-3-sulphonic acid has been synthesized and adsorption behavior for heavy metal ions has been investigated by batch and column experiment. The guargum 5- amino-1-naphthol-3-sulphonic acid resin can selectively separate heavy metal ions from industrial waste water. The GANSA resin was characterization the basis of ion exchange capacity IR spectra and thermogravimetric analysis.The GANSA resin has been used for removal of heavy metal ions Cd+2,Pb+2,Cu+2,Zn+2in aqueous solution and effluents of Prince Steel Industry,Jodhpur